2015
DOI: 10.5897/ajar2014.9344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Faba bean (Vicia faba L.) varieties against chocolate spot (Botrytis fabae) in North Gondar, Ethiopia

Abstract: Faba bean (Vicia fabae L.) is one of the earliest domesticated food legumes in the world, probably in the late Neolithic period. The crop is also called by several local names (broad bean, horse bean and field bean). The wild progenitor and the exact origin of faba bean still remain unknown. Cultivated faba bean is mainly used as human food in developing and as animal feed in industrialized countries. The objective of this study is to evaluate and identify adaptive, high-yielding and disease resistant Fababean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…It is the oldest legume in the Mediterranean countries. It is used for both human food and animal feed since it contains approximately 30% of protein (Tewodros et al 2015). Besides, faba bean can be used as an efficient crop improving by introducing the grain legumes into crop rotation (Kharrat and Ouchari 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is the oldest legume in the Mediterranean countries. It is used for both human food and animal feed since it contains approximately 30% of protein (Tewodros et al 2015). Besides, faba bean can be used as an efficient crop improving by introducing the grain legumes into crop rotation (Kharrat and Ouchari 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, short grain filling period resulted from short days to flowering and maturity which is an advantage if any terminal moisture stress encountered in the environment(s). Likewise, it was reported that faba bean genotypes took 61 -65 days for days to 50 % flowering and 130-143 days to 90% maturity (Tewodros et al, 2015), and 57 to 63 and 137 to 146 days to 50% flowering and days to 90% maturity, respectively (Million, 2012). Partially in agreement with this finding Million (2012) and Tekle et al (2016), reported grain filling period of faba bean genotypes that ranged from 78 to 87 and 75 to 88 days, respectively.…”
Section: Phenological and Development Of Genotypesmentioning
confidence: 98%
“…Faba bean is used as a major source of protein rich foods in the developing countries for subsistence farmers (Asnakech et al, 2016;Mesfin, 2019) and as animal feed in industrialized countries (Duc et al, 2010;Tewodros et al, 2015). The crop is also a source of cash to the farmers and foreign currency to Ethiopia (Asnakech et al, 2016;Gemechu et al, 2016;Tewodros et al, 2015). Faba bean is widely used in rotation with cereals and other crops as it fixes atmospheric nitrogen (Gemechu et al, 2016;Mesfin, 2019;Tewodros et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The crop is also a source of cash to the farmers and foreign currency to Ethiopia (Asnakech et al, 2016;Gemechu et al, 2016;Tewodros et al, 2015). Faba bean is widely used in rotation with cereals and other crops as it fixes atmospheric nitrogen (Gemechu et al, 2016;Mesfin, 2019;Tewodros et al, 2015). Realizing the potential importance of the crop, nationally 34 improved faba bean varieties have been released for production with appropriate management practices (Mesfin, 2019).…”
Section: Introductionmentioning
confidence: 99%